Sex Determination from Hand Dimensions in Nepalese Medical Students: A Cross-Sectional Study - Kandel, Jwala; Parajuli, Sudhir Raman (Nepal Journal of Medical Sciences, 2026)
Introduction: Sex determination is one of the important parts of forensic investigation other than race, age and stature especially when mutilated, decomposed and skeletonized human remains are encountered. Studies in various populations have shown hand dimensions to be useful in sex differentiation. Present study aims at determining sex from hand dimensions in Nepalese medical students.Methods: This was cross sectional study was conducted from February 2024 to August 2025 in Nobel Medical College Teaching Hospital, Nepal, including 412 Nepalese medical students (182 males and 230 females). Hand length and hand breadth were measured and hand index calculated. Data was analyzed using SPSS (Ver.20) software. Male and female parameters were compared using independent sample t-test. P value < 0.05 was considered significant. The average value of male and female was set as sectioning point for each parameter to calculate the diagnostic accuracy of sex determination.Results: Males had significantly greater hand length, hand breadth and hand index (P < 0.001) with sectioning points calculated as 17.84cm, 7.96cm and 44.59 respectively for sex differentiation. Discriminant analysis showed diagnostic accuracy of hand breadth, hand index and hand length to be 89.6%, 81.3% and 79.1% for females and 78%, 74.7% and 72% for males respectively in determining sex.Conclusions: Sex differentiation by sectioning point analysis of hand dimensions is reasonably accurate in Nepalese medical students. Hand breadth is the most accurate followed by hand index and hand length. Diagnostic accuracy is greater in females than males